Correction of Sagittal Craniosynostosis Using Distraction Osteogenesis Based on Strategic Categorization. Issue 1 (January 2017) - Lee, Myung Chul; Shim, Kyu Won; Yun, In Sik; Park, Eun Kyung; Kim, Yong Oock
Abstract : Background: Distraction osteogenesis has been used to correct sagittal craniosynostosis in various ways. The purpose of this study was to introduce three distraction osteogenesis procedures by describing four objective measurements. Methods: Fifty-four patients with sagittal synostosis were recruited and assigned to one of three therapeutic groups: group 1, anteroposterior compression with bitemporal expansion ( n = 35); group 2, bitemporal expansion ( n = 9); and group 3, anteroposterior expansion with bitemporal expansion ( n = 10). Distraction procedures were performed while maintaining dural attachment. Four indices—namely cranial index, head circumference, intracranial volume, and neurodevelopmental index (using the Bayley Scales of Infant Development II), were analyzed. Results: The preoperative cranial index of group 1 (68.51 ± 4.73) differed significantly from those of groups 2 (76.75 ± 2.4; p < 0.05) and 3 (86.8 ± 3.99; p < 0.05). Postoperative cranial index in all groups converged to the mesocephalic cranial index. Preoperative intracranial volume determinations were within the normal range for the majority of participants in groups 1 and 2; however, most fell below −1 SD in group 3 [ n = 8 (80 percent)]. Postoperatively, 90 percent of group 3 participants had intracranial volume values within the normal range. The preoperative mental and psychomotor developmental indices of group 3 were significantly lower than those in the other two groups. The postoperative analysis showed significant improvement in these indices in groups 1 and 3 or when all patients were analyzed. Conclusion: Symmetric sagittal synostosis can be effectively treated with distraction osteogenesis reformation guided by strategic categorization. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.